Member
Patent Information
- Application Number
- JP2023141636
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-31
- Publication Date
- 2025-03-13
AI Technical Summary
【0011】 本発明によれば、水と、有機成分および無機成分を含む汚染物質とが表面に付着し、且つ表面に水と汚染物質とが混在した状態で水が乾燥するというサイクルが繰り返される環境下において、表面への汚れ、とりわけ水垢およびタンパク質の付着または固着を抑制することができ、さらに付着した汚れを容易に、すなわち小さい清掃負荷で除去することができる部材が提供される。
Smart Images

Figure 2025034942000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a member, specifically to a member intended to be used in an environment in which water and contaminants containing organic and inorganic components adhere to a surface, and the water dries while the water and contaminants are still mixed on the surface, resulting in a repeated cycle. [Background technology]
[0002] When tap water adheres to the surface of a component used in an environment where it may be exposed to water and dries, the inorganic components contained in the tap water adhere to the surface and form limescale. A typical inorganic component is silicate ions (SiO3 2- ) and calcium ions (Ca 2+ ) Silicate ion (SiO3 2- ) are polymerized by dehydration condensation, and calcium ions react with CO2 in the air or water, densely crystallizing as calcium carbonate as the water evaporates, and these adhere to the surface of the component, either alone or as a mixture, to form limescale. When a large amount of water adheres to the surface of the component, or when water is repeatedly applied to and dried on the surface of the component, the amount and frequency of silicate ions and calcium ions adhering to the surface of the component increases, accelerating the formation of limescale and resulting in a state in which limescale adheres strongly to the surface of the component, i.e., the limescale is fixed to the surface of the component.
[0003] In addition to water, various contaminants such as the inorganic components (silicate ions, calcium ions, etc.) and organic components (sebum, soap scum, rinse, proteins, etc.) mentioned above adhere to the surface of the component. These contaminants remain on the surface of the component when the water dries. In many cases, at least one or more types of these contaminants adhere to the surface of the component, and a mixture of water stains and contaminants is formed on the surface of the component after drying. Technologies for modifying the surface of the component have been proposed to suppress the adhesion of such contaminants and to improve the cleanability of adhered contaminants.
[0004] For example, JP 2008-239949 A (Patent Document 1) discloses a hydrophilic member having a surface excellent in antifouling properties, antifogging properties and abrasion resistance. Specifically, the member discloses a hydrophilic film formed on a substrate by bonding a zwitterionic low molecular weight compound having a betaine structure to a hydrophilic polymer having a silane coupling group at the end or side chain by silane coupling, and introducing inorganic components such as Si, Ti, Zr, and Al for densification.
[0005] In addition, WO2018 / 079592 (Patent Document 2) discloses a laminate sheet having a substrate layer and a hydrophilic coating layer formed using a resin composition containing an aqueous polyester resin and a zwitterionic polymer. This laminate sheet is said to be resistant to fogging and has excellent antifouling properties.
[0006] In addition, WO2018 / 155577 (Patent Document 3) discloses a hydrophilic structure having a layer structure in which a substrate, an intermediate layer, and a hydrophilic layer are laminated in this order, the intermediate layer being a layer containing a siloxane-based polymer, and the hydrophilic layer containing a zwitterionic polymer having no silicon atoms. This structure is said to have excellent hydrophilicity, stain resistance, adhesion, and water resistance.
[0007] In addition, WO2017 / 018146 (Patent Document 4) discloses a member in which a coating is formed on a substrate by curing a curable composition containing a polyfunctional (meth)acrylamide monomer and an acrylic or acrylamide betaine monomer. This member is said to be capable of exhibiting excellent anti-fogging properties and to have excellent anti-fogging durability while maintaining high hardness. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] JP 2008-239949 A [Patent Document 2] WO2018 / 079592 publication [Patent Document 3] WO2018 / 155577 publication [Patent Document 4] WO2017 / 018146 publication Summary of the Invention [Problem to be solved by the invention]
[0009] The present inventors have focused on the fact that proteins are present at a high ratio among various contaminants present on the surface of components used in an environment where water and contaminants containing organic and inorganic components adhere to the surface, and the water dries while the water and contaminants are mixed on the surface, and this cycle is repeated. For example, human-derived keratin is a typical protein that occurs in a bathroom environment. Proteins have hydrophobic regions, positively charged regions, and negatively charged regions in their molecules, so they can adhere to inorganic materials such as glass and ceramics, resin materials, and metal materials that are commonly used as wet-area components, by hydrophobic action, electrostatic action, and the like. For this reason, proteins were considered to be the main contaminants. Then, the inventors came up with the idea that it is important to suppress the adhesion of proteins, which are such main contaminants, to the surface of components. Therefore, it was first confirmed that the adhesion of proteins can be suppressed by including a betaine structure on the surface of the component. However, it was found that by incorporating a betaine structure into the surface of a component, a specific problem occurs in the component used in an environment where water and contaminants containing organic and inorganic components adhere to the surface, and the water dries while the water and contaminants are mixed on the surface, and this cycle is repeated. That is, a new problem was found that by incorporating a betaine structure into the surface of a component, the formation of water scale is promoted. Therefore, it was found that by controlling the structure and content of the betaine to be incorporated into the surface of the component, and further limiting the content of the component that fixes water scale (inorganic elements such as Si), it is possible to suppress the adhesion of proteins and the formation of water scale at the same time, thereby solving the above problem. The present invention is based on these findings. [Means for solving the problem]
[0010] The component according to the invention comprises: A member used in an environment where water and contaminants including organic and inorganic components adhere to a surface, and the water dries while the water and contaminants are mixed on the surface, the cycle being repeated, The member includes a substrate and a surface layer, The surface layer includes a structure represented by the following formula (A1): [ka] In formula (A1), L1 is -COO-, -CONH-, -(CH2) m - (where m is a natural number), R1 is H or CH3; X1 is a functional group represented by the following formula (B1) or the following formula (B2), [ka] [ka] In formula (B1), R3 and R6 each independently represent -(CH2) l - (l is a natural number from 1 to 10), R4 and R5 are each independently an organic group that contains C and H as essential components and O as an optional component, but does not contain N or S; In formula (B2), R7 and R8 each independently represent -(CH2) l - (l is a natural number from 1 to 10), R9, R 10 , R 11 are each independently an organic group containing C and H as essential components and O as an optional component, and not containing N or S, The surface of the component is measured by X-ray photoelectron spectroscopy (XPS): N+ N atoms belonging to (hereinafter referred to as "N + The concentration of 0.3% or more and 2.8% or less of the metal elements (referred to as "atoms" in this specification) is between 0.3% and 2.8%; The concentration of S atoms, the concentration of P atoms, or the sum of the concentrations of S atoms and P atoms is 0.3% or more; and The concentration of Si atoms is 1.0% or less, The concentration of Si atoms obtained by measuring the region from the surface of the member to a depth of 1 μm using X-ray photoelectron spectroscopy (XPS) is 1.0% or less. It is characterized by: Effect of the Invention
[0011] According to the present invention, a component is provided that can suppress the adhesion or fixation of dirt, particularly limescale and protein, to a surface in an environment in which water and contaminants including organic and inorganic components adhere to a surface and the water dries while the water and contaminants are mixed on the surface, and further allows the adhered dirt to be easily removed, i.e., with a small cleaning load, in an environment in which this cycle is repeated. [Brief description of the drawings]
[0012] [Figure 1] FIG. 2 is a schematic cross-sectional view of an example of a member according to the present invention. [Diagram 2] 1 is a micrograph of a measurement sample of Example 1. [Diagram 3] 1 is a micrograph of a measurement sample of Comparative Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] Materials FIG. 1 is a schematic cross-sectional view of an example of a member according to the present invention (hereinafter, sometimes simply referred to as a "member") that is used in an environment in which water and contaminants containing organic and inorganic components adhere to the surface, and the water dries while the water and contaminants are mixed on the surface, and this cycle is repeated. The member 10 according to the present invention comprises a substrate 1. The member 10 further comprises a surface layer 2. The surface layer 2 is preferably located on the outermost surface of the member 10. The member 10 may further comprise an intermediate layer 3 and / or a primer layer 4, which will be described later. The member 10 may further comprise layers other than those described above (not shown) within a range in which the effects of the present invention can be achieved. The presence of the surface layer 2 in the member 10 can be confirmed by observing the cross section of the member 10 using an electron microscope and separating the layers.
[0014] Purpose The member according to the present invention can be generally applied to members used in wet areas. Examples of wet areas include bathrooms, toilets, washrooms, and kitchens. Specific examples of wet area members for bathrooms include floors, bathtubs, walls, ceilings, counters, aprons, drains, mirrors, etc.; for toilets, toilet bowls, tanks, toilet lids, toilet seats, heated toilet seats, etc.; for washrooms, wash basins, wash counters, mirrors, lighting, plumbing fixtures, drains, cabinets, washing machine pans, etc.; for kitchens, sinks, counters, plumbing fixtures, drains, dishwashers, dish dryers, cooking ranges, kitchen hoods, ventilation fans, etc.
[0015] The member according to the present invention is a member used in an environment where a cycle is repeated in which water and pollutants containing organic and inorganic components adhere to the surface, and the water dries in a state where the water and pollutants are mixed on the surface. Preferably, the member is used in the above environment indoors. For example, the member is used in an environment where a cycle is repeated in which water, components constituting limescale (silicic acid ions, calcium ions, etc.) and proteins adhere to the surface of the member, and the water dries in a state where they are mixed. In addition, the present invention is applicable in a situation where the above cycle is repeated. For example, in the case where the member is a bathtub, the filled state (a state where water and pollutants adhere to the surface) and the drained state (a state where water dries in a state where water and pollutants are mixed) may be maintained in one state for a long time and then transition to another state, or the two states may exist unevenly, but the present invention is applicable even in such cases. The member according to the present invention can effectively suppress not only protein adhesion but also limescale adhesion in such an environment. Here, the contaminant refers to all kinds of dirt that adheres to the surface of a member used in an environment where water is repeatedly attached and dried, and more specifically, means one or more selected from silicate ions, calcium ions, sebum, soap scum, rinse, and protein. The member according to the present invention can be used with any substrate material that is generally used in a member used in an environment where water and contaminants are attached and the water dries in a mixed state, regardless of the type of substrate, and can achieve the above-mentioned effects on various substrates.
[0016] surface layer In the present invention, the surface layer is characterized by including a structure represented by the following formula (A1). [ka] In formula (A1), L1 is -COO-, -CONH-, -(CH2) m - (where m is a natural number), R1 is H or CH3; X1 is a functional group represented by the following formula (B1) or the following formula (B2), [ka] [ka] In formula (B1), R3 and R6 each independently represent -(CH2) l - (l is a natural number from 1 to 10), R4 and R5 are each independently an organic group that contains C and H as essential components and O as an optional component, but does not contain N or S; In formula (B2), R7 and R8 each independently represent -(CH2) l - (l is a natural number from 1 to 10), R9, R 10 , R 11 are each independently an organic group containing C and H as essential components and O as an optional component, and containing no N or S.
[0017] Furthermore, the component according to the invention can be obtained by measuring its surface by X-ray photoelectron spectroscopy (XPS): N + The concentration of the atoms is 0.3% or more and 2.8% or less, The concentration of S atoms, the concentration of P atoms, or the sum of the concentrations of S atoms and P atoms is 0.3% or more. A specific method for measuring the atomic concentrations will be described later, but these characteristics mean that controlling the content of the structure represented by formula (A1) (betaine structure) contained in the surface layer is important for achieving the above-mentioned effects of the present invention, and by controlling the content of the betaine structure within the above range using the concentration of each atom contained in the structure as an index, it is possible to obtain the effect of simultaneously suppressing protein adhesion and limescale adhesion.
[0018] Furthermore, the component according to the present invention is characterized in that it does not contain more than a predetermined amount of Si atoms, which are prone to cause water stains to adhere, and that the concentration of Si atoms obtained by measuring its surface by X-ray photoelectron spectroscopy (XPS) is 1.0% or less.
[0019] As the surface layer satisfies the above characteristics, the member according to the present invention can suppress the adhesion of various contaminants to the surface. In particular, it is possible to suppress both the adhesion of proteins and the fixation of limescale. The mechanism of these suppressions is thought to be as follows, but this is merely a hypothesis, and the present invention is not limited by this hypothesis in any way. The structure represented by formula (A1) is a betaine structure, as described below, and has anti-fouling properties (the ability to suppress the adsorption of proteins). This performance makes it possible to suppress the adhesion of proteins to the surface of the member. On the other hand, the N in the structure represented by formula (A1) + There is a risk that silicate ions will electrostatically adsorb to the surface of the surface. In this case, the amount of silicate ions attached will increase. In other words, the attachment density of the silicate ions will increase. This will induce or promote polymerization due to dehydration condensation between the silicate ions. If the attachment density of the silicate ions increases further in this state, the polymer produced will become denser, which may accelerate the adhesion of water stains. However, the surface layer of the member according to the present invention can be made to have a high N content by controlling the content of the structure represented by formula (A1). +Since the amount of sites is not too large and the atomic concentration of Si and the like is also controlled, the number of adsorption points of silicate ions can be reduced, and as a result, polymerization of silicate ions and further densification of the generated polymer can be suppressed. The surface layer of the member according to the present invention preferably contains a betaine structure represented by formula (A1) and further contains other organic components. By including an organic component other than a betaine structure, the content of the structure represented by (A1) contained in the surface layer can be controlled, thereby suppressing or preferably blocking polymerization of silicate ions and further densification of the generated polymer, and as a result, adhesion of water scale to the surface of the member can be suppressed. With this mechanism, the member according to the present invention can simultaneously suppress not only adhesion of proteins but also adhesion of water scale. In the present invention, it is more preferable that the structure represented by formula (A1) and other organic components are randomly present in the surface layer.
[0020] In the present invention, the surface layer containing a structure represented by formula (A1) means that the surface layer contains one or more types of a specific number of structures represented by formula (A1).
[0021] In the present invention, the surface layer is preferably a polymer layer. The polymer layer is a layer containing a polymer compound. In the present invention, the surface layer preferably contains a polymer compound containing a structure represented by formula (A1). In the surface layer, it is more preferable that the structure represented by formula (A1) and a structure containing any other organic component are randomly bonded. That is, the surface layer preferably contains a random copolymer of the structure represented by formula (A1) and a structure containing an organic component other than the structure represented by formula (A1). The state in which these structures are randomly bonded can be determined by observing the surface to see that the structure represented by formula (A1) is not locally unevenly distributed.
[0022] The surface layer contains a random copolymer. 13Using C-NMR, it is possible to perform qualitative analysis of copolymer species and quantitative analysis of monomer sequence fraction (mol), monomer composition ratio (mol%, wt%), etc. For example, when the structure represented by formula (A1) is Z and the structure containing an organic component other than the structure represented by formula (A1) is S, if a ZSZ or SZS sequence is present, the surface layer contains random copolymerization.
[0023] The structure represented by formula (A1) and the structure containing an organic component other than the structure represented by formula (A1) will be further explained.
[0024] A structure represented by formula (A1) In formula (A1), L1 is preferably -COO-. This can further suppress protein adhesion and water stain adhesion. When L1 is -CONH-, protein adhesion or water stain adhesion may occur starting from the N that constitutes -CONH-. Also, when L1 is -(CH2) m If -, the hydrophobicity is increased and protein adhesion may occur.
[0025] In the structure represented by formula (A1), X1 is preferably a functional group represented by formula (B1). This can further suppress the adhesion of proteins and the fixation of limescale. Even if X1 is a functional group represented by formula (B2), it is effective, but since the sulfonic acid group contained in formula (B1) exists as a resonance hybrid due to the delocalization of the unpaired electron and is very stable, it is assumed that it has low reactivity with contaminants such as silicate ions and proteins, and therefore has a higher effect.
[0026] In X1 of formula (A1), that is, in formula (B1) or formula (B2), l of R3, R6, R7, and R8 is preferably 1 to 6, more preferably 1 to 5, and even more preferably 1 to 3. This allows cationic N + Adsorption of anionic silicate ions and / or anionic SO3 - Site or PO4 -The adsorption of cationic calcium ions to the site can be minimized. This allows the structure represented by formula (A1) to form a stable molecule. That is, the cationic N + The anionic SO3 site at the end of the structure represented by formula (A1) - PO4 in the site or formula (A1) - Since the distance from the site is not too large, the anionic silicate ions and / or cationic calcium ions are prevented from easily approaching the structure represented by formula (A1) (i.e., the surface layer), and the adsorption of the anionic silicate ions and / or cationic calcium ions can be suppressed.
[0027] The structure containing an organic component other than the structure represented by formula (A1) is preferably represented by the following formula (A2). [ka] In formula (A2), L2 is -COO-, -CONH-, -(CH2) m -(m is a natural number), -Ph- (phenyl group), R2 is H or CH3; X2 preferably contains any structure selected from the group consisting of the following formula (C), the following formula (F1), the following formula (F2), the following formula (G), and the following formula (H). [ka]
[0028] In formula (C), Y is a linear, branched or cyclic hydrocarbon group having 1 to 10 carbon atoms; a is a natural number, R 12 includes any structure selected from the group consisting of H, CH3, C2H5, and the following formula (D1), the following formula (D2), the following formula (D3), and the following formula (D4). [ka] [ka] [ka] [ka]
[0029] In formula (D1), Y is a linear, branched or cyclic hydrocarbon group having 1 to 10 carbon atoms; L3 is -OCO-, -NHCO-, -(CH2) m - (where m is a natural number), R2 is H or CH3.
[0030] In formula (D2), Y is a linear, branched or cyclic hydrocarbon group having 1 to 10 carbon atoms; X3 is a structure represented by the following formula (E1). [ka] In formula (E1), Y is a linear, branched or cyclic hydrocarbon group having 1 to 10 carbon atoms; L3 is -OCO-, -NHCO-, -(CH2) m - (where m is a natural number), R2 is H or CH3; a is a natural number.
[0031] In formula (D3), Y is a linear, branched or cyclic hydrocarbon group having 1 to 10 carbon atoms; X3 is a structure represented by the above formula (E1).
[0032] In formula (D4), X4 is a structure represented by the following formula (E2). [ka] In formula (E2), Y is a linear, branched or cyclic hydrocarbon group having 1 to 10 carbon atoms; L3 is -OCO-, -NHCO-, -(CH2) m - (where m is a natural number), R2 is H or CH3; a is a natural number.
[0033] [ka] [ka] In formula (F2), R 13 is an organic group containing C and H as essential components, O as an optional component, and not containing N or S [ka] In formula (G), R 14 is -(CH2) l - (l is a natural number from 1 to 10), R 15 , R 16 , R 17 are each independently an organic group containing C and H as essential components and O as an optional component, and containing no N or S.
[0034] [ka] In formula (H), R 18 is a straight-chain, branched-chain, or cyclic hydrocarbon group having 1 to 10 carbon atoms.
[0035] The structure containing an organic component other than the structure represented by formula (A1) does not itself actively act on contaminants, but its main role is to dilute the concentration of the betaine structure in the surface layer. Among them, a (meth)acrylic structure is preferable, and a hydrophilic structure is even more preferable. Specifically, as a characteristic of the surface layer, it is more preferable that the static contact angle of water with the surface of the surface layer is 35° or less. The (meth)acrylic structure increases the compatibility with the structure represented by formula (1) and facilitates random copolymerization, and the hydrophilicity does not impair the effect on proteins and the like that contain a large amount of hydrophobic organic components. This improves the effect of suppressing adhesion of organic components such as proteins.
[0036] In addition, as a resin component that is commonly used as an organic component of a structure containing an organic component other than the structure represented by formula (A1), a polyester-based structure as represented by the following formula (N) can be mentioned, but it is preferable that the present invention does not contain this structure. As a non-limiting reason, it is presumed that the polyester-based resin component contains many O atoms, which become adsorption points for silicate ions and easily form water scale. In the present invention, it is preferable that the concentration of O atoms obtained by XPS measurement is 40% or less, and within this range, the desired effect can be exhibited without any problems. [ka]
[0037] In the present invention, whether the surface layer contains the structure represented by formula (A1) can be specified by any one of the following methods or a combination of multiple methods.
[0038] <Infrared spectroscopy (IR)> By measuring the infrared absorption spectrum near the surface of the surface layer by infrared spectroscopy, the functional groups contained in the surface layer can be estimated. For example, the presence of -C=O and -C-O- in the ester bond (-COO-) can be specified from the absorption wave number. As a method for measuring the infrared absorption spectrum near the surface of the surface layer, there are methods such as collecting the surface layer by scraping it off and measuring this powder by the transmission method, and as a more convenient method, the single reflection ATR method, the microscopic ATR method, and the like.
[0039] <Time-of-Flight Secondary Ion Mass Spectrometry (TOF-SIMS)> By TOF-SIMS, the structural information of the organic substances present on the surface of the surface layer can be obtained. By evaluating the surface layer by TOF-SIMS, it is possible to specify the partial structure from the fragment peaks specific to the structure represented by the formula (A1). For example, when the structure represented by the formula (A1) is the structure represented by the following formula (A1-1), fragment peaks specific to m / z = 279.11 and m / z = 421.26 can be detected. When measuring by TOF-SIMS, in order to remove the dirt on the sample surface to be measured, as a pretreatment, the sample surface is sputtered by several nm using an ion source such as a gas cluster ion beam (GCIB), and then Bi3 2+ and other primary ion sources are irradiated, and the fragments are measured.
Chemical formula
[0040] <X-ray Photoelectron Spectroscopy (XPS)> By XPS, it is possible to identify the composition ratio and chemical bond state of C, N, O, and S contained in the molecules constituting the surface layer. For example, the XPS spectrum (N1s orbital) of N atoms derived from a sulfobetaine structure as shown in formula (A1-1) has a peak position at a binding energy of 401.5 eV when no other ionic mixtures are present. In contrast, when the structure represented by formula (A1) is a structure as shown in the following formula (A3) (a structure containing a cationic ammonium moiety) or a mixture of formula (A3) and the following formula (A4) (a structure containing an anionic sulfonic acid moiety), the peak positions are 402.0 eV and 401.8 eV, respectively. In this way, it is possible to identify whether or not an N atom is derived from sulfobetaine based on the difference in peak position. Similarly, it is possible to identify whether S atoms are derived from sulfobetaine from the peak position. The XPS spectrum (S2p orbital) of S atoms derived from the structure shown in formula (A1-1) has a peak position at a binding energy of 166.2 eV, whereas the peak positions are 167.5 eV and 167.1 eV for the structure shown in formula (A4) (anionic sulfonic acid) or a mixture of formulas (A3) and (A4). All of these peak positions are obtained by correcting with the peak position of the C1s orbital at 284.5 eV. [ka] [ka]
[0041] <Nuclear magnetic resonance measurement (NMR)> NMR can provide information on the bonding state of H, C, and N contained in the molecules that make up the surface layer and their interactions with neighboring atoms through chemical shifts compared with standard samples, allowing the molecular structure that makes up the surface layer to be identified in detail.
[0042] Static contact angle of the surface layer In the present invention, the static contact angle of water with the surface of the surface layer is preferably as low as possible. Specifically, it is preferably 35° or less, more preferably 30° or less, and even more preferably 20° or less. This increases hydrophilicity, making it possible to prevent adhesion of various contaminants including proteins.
[0043] The static contact angle of water with respect to the surface of the surface layer is measured, for example, using the following device and software under the following measurement conditions. Equipment: DMo-702 (Kyowa Interface Science Co., Ltd.) Software: FAMAS integrated interface measurement / analysis system Version:7.3.0 Measurement method: Droplet method Droplet volume: 2.0μL Waiting time: 1000ms Analysis method: θ / 2 method
[0044] Proportion of the structure represented by formula (A1) (betaine structure) in the surface layer In the present invention, the content of the structure represented by formula (A1) (betaine structure) in the surface layer is determined by the N + N atoms belonging to (hereinafter referred to as "N + In the present invention, the concentration of N atoms obtained by XPS measurement of the surface of the member is + The concentration of the atoms is from 0.3% to 2.8%, and preferably from 0.4% to 2.6%.
[0045] When the surface layer contains a structure represented by formula (H), the N + The concentration of atoms is N from the structure represented by formula (A1). + The concentration of atoms and N from the structure represented by formula (H) + In such a case, the abundance ratio of the structure represented by formula (A1) (betaine structure) can be determined by the concentration of S atoms, the concentration of P atoms, or the sum of the concentrations of S atoms and P atoms.
[0046] In the present invention, the concentration of S atoms, the concentration of P atoms, or the total of the concentration of S atoms and the concentration of P atoms obtained by performing XPS measurement on the surface of the member is 0.3% or more, and preferably 0.5% or more.
[0047] In the present invention, the concentration of Si atoms obtained by performing XPS measurement on the surface of the member is 1.0% or less. Since the concentration of Si atoms contained in the surface of the member is low, the formation and adsorption of scale can be suppressed. The concentration of Si atoms is preferably 0.7% or less.
[0048] <XPS Measurement> · Preparation of Measurement Sample A measurement sample can be a flat plate-shaped region cut from a member sample with an appropriate size. It is preferable to clean the surface of the measurement sample before measurement. For example, it is more preferable to clean the surface of the measurement sample using a neutral detergent and a sponge, and then thoroughly rinse it with ultrapure water. · XPS Measurement Device For the XPS measurement device, K-alpha (manufactured by ThermoFisher Scientific Co., Ltd.) can be used. · XPS Measurement Conditions X-ray Conditions: Monochromatized AlKα ray, 72W - 12KV Photoelectron Extraction Angle: 90° Analysis Region: 400μmφ Neutralization Gun Conditions: 200μA Ion Gun Conditions: 10mA (Survey) Time per step: 10ms Energy step size: 1.000eV Sweep: 2 times Pass energy: 200eV Scanning Range: -10~1350eV (Narrow) Time per step: 50ms Energy step size: 0.100eV Sweep: 5 times Pass energy: 50eV Scanning range: C1s peak 279.000 eV to 298.000 eV, O1s peak 525.000 eV to 545.000 eV, N1s peak 392.000 eV to 410.000 eV, S2p peak 157.000 eV to 175.000 eV, Si2p peak 95.000 eV to 110.000 eV, P2p peak 124.000 eV to 144.000 eV
[0049] <Calculation of atomic concentrations of each atom (S, N, Si, P)> The atomic concentrations of the detected elements can be calculated from the obtained spectra using, for example, data analysis software Thermo Avantage (version 5.9916, manufactured by Thermo Fisher Scientific Co., Ltd.). First, use the spectrum obtained from the survey analysis to confirm whether the cleaning has been properly performed. Next, perform charge correction on the spectrum obtained from the narrow analysis with the C1s peak set to 284.5 eV. Then, after removing the background by the Smart method for the peaks based on the electron orbits of each measured atom, calculate the peak area intensity and perform an analysis process of dividing by the sensitivity coefficient specific to the device preset in the data analysis software, and calculate the atomic concentration of each atom when the total of C atoms, O atoms, N atoms, S atoms, Si atoms, and P atoms is 100%.
[0050] <Peak separation of N atoms> For separating the peak derived from the +1-valent N atom (N + ) contained in the betaine structure from the peak derived from other 0-valent N atoms (N 0 ), the following method can be used. Fix the peak position of N + at 401.4 to 401.8 eV and the full width at half maximum of the peak at 1.6 eV, fix the peak position of N 0 at 398.7 to 399.4 eV, and perform peak fitting. Calculate the atomic concentrations of N + , N 0 respectively from the results of the peak fitting.
[0051] In the present invention, the surface layer may be provided on the substrate. The surface layer may be provided on the surface of the substrate. In other words, the surface layer may be formed directly on the surface of the substrate without including any other layer between the substrate and the surface layer. When the surface layer is provided on the surface of the substrate, the surface layer is preferably a gradient film with a gradient composition. Specifically, the surface side of the surface layer preferably includes a structure represented by formula (A1), and the substrate side of the surface layer preferably includes a gradient film whose main chain contains a large amount of acrylic resin or polyvinyl resin, as described later. This makes it possible to ensure close contact with the substrate while suppressing the adsorption of proteins and the formation or adsorption of water scale.
[0052] Composition for forming surface layer In the present invention, the surface layer is preferably a cured surface layer forming composition. In the present invention, the surface layer forming composition may contain a compound having a betaine structure, a polymerization initiator, a polymerizable organic compound other than betaine, and a solvent.
[0053] Compounds with a betaine structure In the present invention, the composition for forming a surface layer can contain a compound having a betaine structure. This allows the surface layer obtained by curing the composition for forming a surface layer to contain a structure represented by formula (A1). In the present invention, a compound having a betaine structure means a compound having at least one or more cations, anions, and an ethylenically unsaturated group in the same molecule. In the present invention, examples of the cation include cations such as quaternary ammonium, sulfonium, and phosphonium. Examples of the anion include -COO - , -PO4 2- , -HPO4 - , -SO3 - Examples of anions include:
[0054] In the present invention, the compound having a betaine structure contains a quaternary ammonium as a cation in the molecule and -SO3 as an anion. -Sulfobetaine containing quaternary ammonium as the cation and -PO4 as the anion in the molecule 2- Among them, phosphobetaines containing quaternary ammonium as a cation and -SO3 as an anion in the molecule are preferred. - More preferred is a sulfobetaine containing the following: Further preferred is a sulfobetaine having a (meth)acrylic skeleton in the molecule.
[0055] In the present invention, an example of a compound having a betaine structure is compound 1 represented by the following formula (I1). Compound 1: [ka] In Compound 1, L1 includes any one of -COO-, -CONH-, and -(CH2)m- (m is a natural number); R1 is H or CH3; R3 and R6 each independently represent -(CH2) l - (l is a natural number from 1 to 10), R4 and R5 are each independently an organic group that contains C and H as essential components and O as an optional component, and does not contain N or S. It is characterized by: Incidentally, it is possible to specify that L1 contains -COO- from the above-mentioned IR.
[0056] In the present invention, an example of a compound having a betaine structure is compound 2 represented by the following formula (I2). Compound 2: [ka] In compound 2, L1 includes any one of -COO-, -CONH-, and -(CH2)m- (m is a natural number); R1 is H or CH3; R7 and R8 each independently represent -(CH2)l - (l is a natural number from 1 to 10), R9, R 10 , R 11 are each independently an organic group containing C and H as essential components and O as an optional component, and not containing N or S. It is characterized by:
[0057] In the present invention, specific examples of compounds having a betaine structure include 3-[[2-(acryloyloxy)ethyl]dimethylammonio]propane-1-sulfonic acid, 3-[[2-(methacryloyloxy)ethyl]dimethylammonio]propane-1-sulfonic acid, 4-[(3-methacrylamidopropyl)dimethylammonio]butane-1-sulfonic acid, 2-(methacryloyloxy)ethyl 2-(trimethylammonio)ethyl] phosphate, 4-[[2-(methacryloyloxy)ethyl]dimethylammonio]butane-1-sulfonic acid, 3-[(3-acrylamidopropyl)dimethylammonio]propane-1-sulfonic acid, and 3-[(3-methacrylamidopropyl)dimethylammonio]propane-1-sulfonic acid. Among these, 3-[[2-(acryloyloxy)ethyl]dimethylammonio]propane-1-sulfonic acid, 3-[[2-(methacryloyloxy)ethyl]dimethylammonio]propane-1-sulfonic acid, [3-(methacryloylamino)propyl]dimethyl(3-sulfobutyl)ammonium hydroxide, and 2-(methacryloyloxy)ethyl 2-(trimethylammonio)ethyl phosphate are preferred.
[0058] Polymerizable organic compounds other than betaine As a compound for adjusting the concentration of the betaine structure in the surface layer, the following hydrophilic polymerizable compounds and / or non-hydrophilic polymerizable organic compounds can be used. In the composition for forming the surface layer, the polymerizable organic substances other than betaine are N 2 O 3 obtained by XPS measurement of the surface of the member when the surface layer is formed by the manufacturing method of the member described later. +It is preferable that the atomic concentration is 0.3% or more and 2.8% or less, and it is preferable that the static contact angle of water with the surface of the surface layer is 35° or less.
[0059] <Hydrophilic polymerizable compound> As the hydrophilic polymerizable compound, one or more types selected from the nonionic monomers, anionic monomers and cationic monomers described below can be used.
[0060] (Nonionic Monomer) In the present invention, the surface layer forming composition can contain a nonionic monomer. This allows the surface layer obtained by curing the surface layer forming composition to contain a structure containing an organic component other than the structure represented by formula (A1). In the present invention, the nonionic monomer means a monomer having one or more ethylenically unsaturated groups and an oxyalkylene in the molecule. The nonionic monomer is hydrophilic. The nonionic monomer is more preferably a monomer having a (meth)acrylic skeleton and an oxyalkylene group in the molecule.
[0061] In the present invention, the nonionic monomer may be a monofunctional nonionic monomer represented by the following formula (J1). [ka] In formula (J1), L2 is -COO-, -CONH-, -(CH2) m - (where m is a natural number), R2 is H or CH3; R 12 is H or CH3 or C2H5, Y is a linear, branched or cyclic hydrocarbon group having 1 to 10 carbon atoms; a is a natural number.
[0062] In the present invention, the nonionic monomer may be a bifunctional nonionic monomer having an oxyalkylene group, represented by the following formula (J2). [ka] In formula (J2), L2 is -COO-, -CONH-, -(CH2) m - (where m is a natural number), L3 is -OCO-, -NHCO-, -(CH2) m - (where m is a natural number), R2 is H or CH3; Y is a linear, branched or cyclic hydrocarbon group having 1 to 10 carbon atoms; a is a natural number.
[0063] In the present invention, the nonionic monomer may be a trifunctional nonionic monomer 1 having an oxyalkylene group, represented by the following formula (J3). [ka] In formula (J3), L3 is -OCO-, -NHCO-, -(CH2) m - (where m is a natural number), R2 is H or CH3; Y is a linear or cyclic hydrocarbon group having 1 to 10 carbon atoms; b, c, and d are each independent natural numbers.
[0064] In the present invention, the nonionic monomer may be a trifunctional nonionic monomer 2 having an oxyalkylene group, represented by the following formula (J4). [ka] In formula (J4), L3 is -OCO-, -NHCO-, -(CH2) m- (where m is a natural number), R2 is H or CH3; Y is a linear or cyclic hydrocarbon group having 1 to 10 carbon atoms; b, c, and d are each independent natural numbers.
[0065] In the present invention, the nonionic monomer may be a tetrafunctional nonionic monomer having an oxyalkylene group, represented by the following formula (J5). [ka] In formula (J5), L2 is -COO-, -CONH-, -(CH2) m - (where m is a natural number), L3 is -OCO-, -NHCO-, -(CH2) m - (where m is a natural number), R2 is H or CH3; Y is a linear or cyclic hydrocarbon group having 1 to 10 carbon atoms; b, c, d, and e are each independent natural numbers.
[0066] In the present invention, specific examples of nonionic monomers include 4-hydroxybutyl acrylate, 2-methoxyethyl acrylate (2-methoxyethyl acrylate), 2-[2-(2-methoxyethoxy)ethoxy]ethyl acrylate, 2-hydroxyethyl methacrylate (2-hydroxyethyl methacrylate (HEMA)), 2-methoxyethyl methacrylate, diethylene glycol monomethyl ether methacrylate, hydroxypropyl methacrylate, 2-hydroxybutyl methacrylate, N-(hydroxymethyl)acrylamide, N-(2-hydroxyethyl)acrylamide, N-(methoxymethyl)acrylamide, N-(methoxymethyl)methacrylamide, N-(hydroxymethyl)methacrylamide, and methoxydiethylene glycol. Methacrylate, methoxytetraethylene glycol methacrylate, methoxypolyethylene glycol methacrylate, methoxypolyethylene glycol acrylate, polyethylene glycol methacrylate, N-(4-hydroxyphenyl)methacrylamide, diethylene glycol dimethacrylate, triethylene glycol dimethacrylate, polyethylene glycol diacrylate, polyethylene glycol dimethacrylate, alkoxylated trimethylolpropane acrylate, alkoxylated trimethylolpropane methacrylate, alkoxylated glycerin acrylate, alkoxylated glycerin methacrylate, alkoxylated pentaerythritol tetraacrylate, and alkoxylated pentaerythritol tetramethacrylate. Of these, 2-hydroxyethyl methacrylate (HEMA), methoxytetraethylene glycol methacrylate, methoxypolyethylene glycol methacrylate, 2-methoxyethyl acrylate, and diethylene glycol dimethacrylate are preferred. More preferred are 2-hydroxyethyl methacrylate (HEMA) and methoxypolyethylene glycol methacrylate.
[0067] (anionic monomer) In the present invention, the composition for forming a surface layer can contain an anionic monomer. This allows the surface layer obtained by curing the composition for forming a surface layer to contain a structure containing an organic component other than the structure represented by formula (A1). In the present invention, the anionic monomer means a compound having at least one or more anions and ethylenically unsaturated groups in the molecule. In the present invention, the anion is -COO - , -PO4 2- , -HPO4 - , -SO3 - Examples of anions include:
[0068] In the present invention, examples of the anionic monomer include anionic monomers represented by the following formulae (K1) and (K2). [ka] In formula (K1), L2 is -COO-, -CONH-, -(CH2) m -, -Ph- (where m is a natural number), R2 is H or CH3; M1 represents a hydrogen ion, an ammonium ion, or an alkali metal ion. [ka] In formula (K2), L2 is -COO-, -CONH-, -(CH2) m -(m is a natural number), -Ph-, R2 is H or CH3; R 13 is an organic group containing C and H as essential components and O as an optional component, and not containing N or S, M1 represents a hydrogen ion, an ammonium ion, or an alkali metal ion.
[0069] In the present invention, specific examples of the anionic monomer include 2-((meth)acryloyloxy)ethanesulfonic acid, potassium 2-((meth)acryloyloxy)ethanesulfonate, sodium 2-((meth)acryloyloxy)ethanesulfonate, 3-((meth)acryloyloxy)propane-1-sulfonic acid, potassium 3-((meth)acryloyloxy)propane-1-sulfonate, sodium 3-((meth)acryloyloxy)propane-1-sulfonate, 2-acrylamido-2-methylpropanesulfonic acid, potassium 2-acrylamido-2-methylpropanesulfonate, sodium 2-acrylamido-2-methylpropanesulfonate, styrenesulfonic acid, potassium styrenesulfonate, and sodium styrenesulfonate.
[0070] (Cationic Monomer) In the present invention, the cationic monomer may be represented by the following formula (L). [ka] In formula (L), L2 is -COO-, -CONH-, -(CH2) m - (where m is a natural number), R2 is H or CH3; R 14 is -(CH2) l - (l is a natural number from 1 to 10), R 15 , R 16 , R 17 are each independently an organic group containing C and H as essential components and O as an optional component, and not containing N or S, M2 represents any one of a hydroxide ion, a fluorine ion, a chloride ion, a bromide ion, and an iodine ion.
[0071] In the present invention, specific examples of the cationic monomer include N-(2-(meth)acryloyloxyethyl)-N-benzyl-N,N-dimethylammonium chloride, (3-(meth)acrylamidopropyl)trimethylammonium chloride, and N-(2-(meth)acryloyloxyethyl)-N-benzyl-N,N-dimethylammonium chloride.
[0072] <Non-hydrophilic polymerizable compound> In the present invention, the non-hydrophilic polymerizable compound may be a non-polar monomer.
[0073] In the present invention, the non-polar monomer may be a monofunctional non-ionic monomer having a hydrocarbon group, represented by the following formula (M). [ka] In formula (M), L2 is -COO-, -CONH-, -(CH2) m - (where m is a natural number), R2 is H or CH3; R 18 is a straight-chain or cyclic hydrocarbon group having 1 to 10 carbon atoms.
[0074] In the present invention, specific examples of non-polar monomers include allyl acrylate, allyl methacrylate, ethyl acrylate, ethyl methacrylate, ethyl acrylamide, ethyl methacrylamide, propyl acrylate, propyl methacrylate, propyl acrylamide, propyl methacrylamide, isopropyl acrylate, isopropyl methacrylate, isopropyl acrylamide, isopropyl methacrylamide, butyl acrylate, butyl methacrylate, butyl acrylamide, butyl methacrylamide, isobutyl acrylate, isobutyl methacrylate, isobutyl acrylamide, isobutyl methacrylamide, tert-butyl acrylate, isobutyl methacrylate, isobutyl acrylamide, isobutyl methacrylamide, and tert-butyl acrylate. Examples of the acrylic acid ester include t-butyl acrylate, tert-butyl methacrylate, tert-butyl acrylamide, tert-butyl methacrylamide, hexyl acrylate, hexyl methacrylate, hexyl acrylamide, hexyl methacrylamide, cyclohexyl acrylate, cyclohexyl methacrylate, cyclohexyl acrylamide, cyclohexyl methacrylamide, benzyl acrylate, benzyl methacrylate, benzyl acrylamide, benzyl methacrylamide, 2-ethylhexyl acrylate, 2-ethylhexyl methacrylate, 2-ethylhexyl acrylamide, and 2-ethylhexyl methacrylamide.
[0075] solvent In the present invention, the composition for forming a surface layer may contain a solvent. This can improve the wettability to the substrate or adjust the viscosity of the composition for forming a surface layer. As the solvent, alcohols such as methanol, ethanol, IPA (isopropanol), and n-butanol, cellosolves such as 2-methoxyethanol and methoxypropanol, ketones such as acetone, DMF (N,N'-dimethylformamide), water, etc. can be used, but are not limited to these. In addition, multiple types of solvents may be mixed and used as necessary. In addition, the solvent can also be used when preparing the composition for forming a primer layer and the composition for forming an intermediate layer, which will be described later.
[0076] Polymerization initiator The surface layer-forming composition preferably contains a polymerization initiator. As the polymerization initiator, known ones can be used, for example, a photopolymerization initiator or a thermal polymerization initiator.
[0077] Preferred examples of the photopolymerization initiator include Irgacure 651, Irgacure 184, Irgacure 500, Irgacure 2959, Irgacure 127, Irgacure 907, Irgacure 369, Irgacure 1300, Irgacure 819, Irgacure 1800, Irgacure OXE01, Irgacure OXE02, Darocur 1173, Darocur TPO, and Darocur 4265, all of which are available from BASF.
[0078] As a preferred example of the thermal polymerization initiator, a thermal radical generator such as a peroxide, a persulfate, or an azo compound is preferably used.
[0079] Additives In addition to the above, the surface layer forming composition may contain known additives such as surfactants depending on the purpose, within the range that does not impair the function of the surface.
[0080] Middle Tier In the present invention, in order to further strengthen the adhesion between the substrate 1 and the surface layer 2, an intermediate layer 3 may be formed between the substrate 1 and the surface layer 2. In order to obtain strong adhesion with the surface layer 2, which is an organic film, the intermediate layer 3 preferably contains a main chain of an acrylic resin (polyacrylic copolymer) or a polyvinyl copolymer containing vinyl alcohol.
[0081] Composition for forming intermediate layer In the present invention, the intermediate layer 3 is preferably formed by curing a composition for forming an intermediate layer. The composition for forming an intermediate layer preferably contains a monomer capable of forming a polyacrylic or polyvinyl copolymer. The composition for forming an intermediate layer preferably further contains the above-mentioned solvent and polymerization initiator.
[0082] <Multi-functional acrylate> As a monomer constituting the polyacrylic copolymer, a multifunctional acrylate can be suitably used. In the present invention, the multifunctional acrylate means a monomer having at least two or more ethylenically unsaturated groups in the molecule. Specific examples of the multifunctional acrylate include 2-hydroxy-3-acryloyloxypropyl methacrylate, propoxylated ethoxylated bisphenol A diacrylate, ethoxylated bisphenol A diacrylate, 9,9-bis[4-(2-acryloyloxyethoxy)phenyl]fluorene, propoxylated bisphenol A diacrylate, tricyclodecane dimethanol diacrylate, 1,10-decane diol diacrylate, 1,6-hexanediol diacrylate, 1,9-nonane diol diacrylate, and the like. All diacrylate, dipropylene glycol diacrylate, tripropylene glycol diacrylate, ethoxylated isocyanuric acid triacrylate, ε-caprolactone modified tris-(2-acryloxyethyl) isocyanurate, pentaerythritol triacrylate, trimethylolpropane triacrylate, ditrimethylolpropane trimethacrylate, ethoxylated glycerin triacrylate, ethoxylated pentaerythritol tetraacrylate, ditrimethylolpropane trimethacrylate Pantaerythritol tetraacrylate, dipentaerythritol hexaacrylate, ethylene glycol dimethacrylate, diethylene glycol dimethacrylate, triethylene glycol dimethacrylate, 2,2 bis [4- (methacryloxyethoxy) phenyl] propane, tricyclodecane dimethanol dimethacrylate, 1,10-decanediol dimethacrylate, 1,6-hexanediol methacrylate, 1,9-nonanediol methacrylate, neopentyl glycol methacrylate, glycerin dimethacrylate, trimethylolpropane trimethacrylate, polyethylene glycol diacrylate, polyethylene glycol dimethacrylate, polypropylene glycol diacrylate, polytetramethylene glycol diacrylate, glycerin triacrylate ethoxylate, dipentaerythritol polyacrylate, ethoxylated polypropylene glycol dimethacrylate, polypropylene dimethacrylate, and the like.
[0083] In addition, the polyfunctional acrylate may be a urethane (meth)acrylate oligomer (polymer) having two or more ethylenically unsaturated groups. For example, phenyl glycidyl ether acrylate hexamethylene diisocyanate urethane prepolymer, phenyl glycidyl ether acrylate toluene diisocyanate urethane prepolymer, pentaerythritol triacrylate hexamethylene diisocyanate urethane prepolymer, pentaerythritol triacrylate toluene diisocyanate urethane prepolymer, pentaerythritol triacrylate isophorone diisocyanate urethane prepolymer, dipentaerythritol pentaacrylate hexamethylene diisocyanate urethane prepolymer, oligourethane acrylate, carboxylic acid-containing urethane acrylate oligomer, etc. may be mentioned.
[0084] In addition, examples of polyfunctional acrylates include epoxy (meth)acrylate oligomers (polymers) having two or more ethylenically unsaturated groups, such as cresol novolac type epoxy acrylates and carboxylic anhydride modified epoxy acrylates.
[0085] In the present invention, a specific example of a preferred polyfunctional acrylate is one in which the functional group equivalent of the ethylenically unsaturated group is 200 g / eq or less. This allows a primer layer with high durability to be obtained. The functional group equivalent of the ethylenically unsaturated group is preferably 150 g / eq or less, more preferably 27 g / eq or more and 150 g / eq or less. This allows a primer layer with higher durability to be obtained. Here, the functional group equivalent represents the molecular weight of a compound per functional group. That is, it is a value obtained by dividing the molecular weight of the polyfunctional acrylate by the number of ethylenically unsaturated groups. Specifically, it is a value obtained by dividing the molecular weight of the polyfunctional acrylate, which is a (meth)acrylate monomer (oligomer), a urethane modified product thereof, a urethane (meth)acrylate monomer (oligomer), and an epoxy modified product thereof, an epoxy (meth)acrylate monomer (oligomer), by the number of (meth)acryloyl groups, which are ethylenically unsaturated groups. Examples of compounds satisfying such functional group equivalents include pentaerythritol tetraacrylate (88 g / eq), dipentaerythritol tetraacrylate (105 g / eq), dipentaerythritol hexaacrylate (96 g / eq), trimethylolpropane triacrylate (99 g / eq), trimethylolpropane tetraacrylate (117 g / eq), 1,3,5-tris(2,2-diacryloyloxymethyl-3-(2,2,2-triacryloyloxymethylethoxy)propylhexylcarbamate)isocyanurate (153 g / eq), and ethoxylated dipentaerythritol hexaacrylate (185 g / eq).
[0086] Among these, those having six or more functional groups in one molecule are particularly preferred in order to further enhance the durability of the intermediate layer, and examples thereof include dipentaerythritol hexaacrylate (6 functional), ethoxylated dipentaerythritol hexaacrylate (6 functional), and 1,3,5-tris(2,2-diacryloyloxymethyl-3-(2,2,2-triacryloyloxymethylethoxy)propylhexylcarbamate)isocyanurate (15 functional).
[0087] <Multifunctional vinyl compounds> As a monomer constituting the polyvinyl copolymer, a multifunctional vinyl compound can be suitably used. In the present invention, the multifunctional vinyl compound means a monomer having at least two ethylenically unsaturated groups in the molecule. Specific examples of the multifunctional vinyl compound include diallyl ether, diethylene glycol divinyl ether, 1,3-diallyloxy-2-propanol, 1,2,3-triallyloxy-2-propanol, 2,2 bisallyloxymethyl-1-propanol, 2,2 bisallyloxyethyl-1-butanol, 2,2 bisallyloxymethyl-1-hexanol, 3,3 bisallyloxyethyl-1-butanol, 3,3 bisallyloxyethyl-1-hexanol, 2, Examples of such alkyl ethers include 2,2-aryloxymethyl-1-ethanol, 2,2,2-aryloxymethyl-1-propanol, 2,2,2-aryloxymethyl-1-butanol, 2,2,2-aryloxymethyl-1-hexanol, 1,5-hexadiene-3,4-diol, diallyl isophthalate, 1,5-hexanediene, tetraallyloxyethane, tetraallyloxypropane, tetraallyloxybutane, triallyl citrate, and divinyl adipate.
[0088] In the present invention, the surface layer and the intermediate layer can be formed simultaneously by using a composition obtained by mixing the composition for forming the surface layer and the composition for forming the intermediate layer. In this case, it is necessary to form the film so that the structure represented by formula (A1) is sufficiently contained in the surface layer. For example, by adding an additive such as a surfactant to the composition, it is possible to cause the structure represented by formula (A1) to be segregated at an inclination on the surface. Here, the surfactant preferably has a hydrophilic portion and a hydrophobic portion consisting of an organic residue, and has a molecular weight of less than 10,000.
[0089] In order to improve the wettability of the surface, it is preferable to use a polymerizable surfactant. Examples of the polymerizable surfactant include polyoxypropylene allyl ether phosphate ester, ammonium salt of ester of sulfuric acid and ethoxylated allyl alkyl glyceryl ether, polyoxyalkylene alkenyl ether, sodium alkyl allyl sulfosuccinate, ammonium salt of polyoxyethylene-1-(allyloxymethyl)alkyl ether sulfate ester, amine salt, and the like.
[0090] In the present invention, the film thickness including the formed surface layer and intermediate layer is preferably in the range of 0.1 μm to 200 μm. Thereby, the effects of suppressing the adhesion of proteins and the adhesion of scale can be sufficiently obtained, and further, abrasion resistance can be exhibited. The film thickness including the surface layer and intermediate layer is more preferably in the range of 1 to 100 μm, and even more preferably in the range of 1 to 20 μm.
[0091] The film thickness of the surface layer can be measured by cross-sectional observation using SEM or the like.
[0092] <Film thickness measurement by SEM> · SEM apparatus For the SEM apparatus, Regulus8220 (manufactured by Hitachi High-Technologies Corporation) can be used and measurement can be performed under the following conditions. · SEM measurement conditions Acceleration voltage: 1 kV Magnification: 20000 - 400 times
[0093] Primer layer In the present invention, when the base material 1 is an inorganic material such as glass, pottery, or metal, a primer layer 4 may be formed in order to strengthen the adhesion between these inorganic materials and the surface layer 2. The primer layer 4 is preferably formed between the inorganic material which is the base material 1 (hereinafter referred to as "inorganic base material") and the surface layer 2. In order to enhance the adhesive strength, the primer layer 4 needs to bond to both the inorganic base material and the surface layer 2. For this reason, the primer layer 4 is preferably a layer containing silicon atoms.
[0094] Primer layer forming composition The primer layer 4 is preferably a cured composition for forming a primer layer. The composition for forming a primer layer may contain a commonly used silane-based or phosphoric acid-based coupling agent. In addition, it is preferable that these coupling agents contain an ethylenically unsaturated group such as an acryloyl group or a methacryloyl group in order to further strengthen the adhesion with the surface layer.
[0095] <Silane compounds> Silane compound can be suitably used as silane coupling agent. In the present invention, silane compound means an organic compound having hydrolyzable Si-OR group (reactive silyl group, OR can be hydroxyl group or hydrolyzable group. Hydrolyzable group is, for example, alkoxy group, halogeno group. Specifically, -OCH3, -OCH2CH3, -Cl can be mentioned.). Specific examples of silane compounds include tetraethoxysilane, 3-acryloxypropyltrimethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-methacryloxypropyltrimethoxysilane, 8-methacryloxyoctyltrimethoxysilane, 3-methacryloxymethyltriethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-methacryloxymethyltrimethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, Silane, 3-glycidoxypropyltriethoxysilane, p-styryltrimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-triethoxysilyl-N-(1,3-dimethyl-butylidene)propylamine, N-phenyl-3-aminopropyltrimethoxysilane, tris-(trimethoxysilylpropyl)isocyanurate, 3-ureidopropyltrialkoxysilane, 3-mercaptopropylmethyldimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-isocyanatopropyltriethoxysilane, 3-trimethoxysilylpropylsuccinic anhydride, and the like.
[0096] In the present invention, a specific example of a preferred silane compound is a compound having three or more hydrolyzable Si-OR groups for adhering to an inorganic substrate and an acrylic or methacrylic polymerizable functional group for adhering to a surface layer that is an organic film. Examples of such silane compounds include 3-acryloxypropyltrimethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-methacryloxypropyltrimethoxysilane, 8-methacryloxyoctyltrimethoxysilane, 3-methacryloxymethyltriethoxysilane, 3-methacryloxypropyltriethoxysilane, and 3-methacryloxymethyltrimethoxysilane.
[0097] <Phosphate compounds> As the phosphate coupling agent, a phosphate compound can be preferably used. In the present invention, the phosphate compound is a compound having a covalent bond P(OH) n It means an organic compound having a group (adsorbent phosphate group, n is any one of 1 to 3, and OH group may be its base substitute such as ONa, OK, ONH4, etc.). As the phosphate compound, those containing phosphoric acid or a phosphate as an adsorbent functional group and an acryl group, methacryl group, or vinyl group as a polymerizable functional group in the molecule are preferable. Specific examples include 2-acryloxyethyl phosphoric acid, 2-acryloxyethyl phosphoric acid, 2-methacryloxyethyl phosphoric acid, 2-methacryloxyethyl phosphoric acid, 2-acryloxypropyl phosphoric acid, 2-acryloxypropyl phosphoric acid, 2-methacryloxypropyl phosphoric acid, 2-methacryloxypropyl phosphoric acid, 2-methacryloxypropyl phosphoric acid, vinyl phosphoric acid, 2-acryloxybutyl phosphoric acid, 2-acryloxybutyl phosphoric acid, 2-methacryloxybutyl phosphoric acid, 2-methacryloxybutyl phosphoric acid, vinyl phosphoric acid, or their phosphates.
[0098] <Optional ingredients> Other optional components may be added to the surface layer, intermediate layer, and primer layer, such as ultraviolet absorbers, light stabilizers, antioxidants, leveling agents, defoamers, thickeners, anti-settling agents, and various additives such as dyes, pigments, and matting agents that control the design properties of the paint, within a range that does not impair the stain resistance of the member.
[0099] Base material In the present invention, the substrate is not particularly limited. As the material of the substrate, any material generally used as a water-related component, such as resin, metal, inorganic material (glass, ceramic, etc.), can be used. In addition, the shape of the substrate can be a general shape of a water-related component. For example, it may be a flat plate or a complex shape.
[0100] Durability of materials (long-term effectiveness) When the member of the present invention is used in a wet area, the member is maintained by rubbing the member with water and a detergent containing water on a sponge, cloth, or the like. It is more preferable that the member of the present invention has a static contact angle of water on the surface layer of 35 degrees or less and a level of 2 or higher in the scale cleanability evaluation after the sliding durability evaluation test described below. This allows the member to have sufficient sliding durability and maintain the effect of suppressing protein adhesion and scale fixation for a long period of time even in the above-mentioned environment. The scale cleanability evaluation will be described in detail later.
[0101] <Sliding durability evaluation> The member according to the present invention can be subjected to a sliding durability test using a sliding machine (manufactured by Tester Sangyo Co., Ltd.) according to the following method. A commercially available urethane sponge (Scotch-Brite Bath Shine, manufactured by 3M Japan Co., Ltd.) is soaked in a mixture of water and neutral detergent (Bath Magiclean, manufactured by Kao Corporation) in a weight ratio of 90:10, and is moved back and forth over the surface of the component 5,000 times with a load of 25 g / cm2. After washing the component with running water, it is dried and the static contact angle of water is measured using the method described above. The durability of the member can be determined as follows: those with durability are marked as ○ and those without durability are marked as × based on the contact angle of water after the sliding durability test and the evaluation result (level) of the scale deposit cleaning property. ○: The static contact angle of water after the sliding test is 35 degrees or less, and the level is 2 or more in the evaluation of the scale deposit cleaning property. ×: The static contact angle of water after the sliding test is greater than 35 degrees, or the level is 1 or less in the evaluation of the scale deposit cleaning property.
[0102] The member of the present invention can exhibit the above-described durability when the concentration of Si atoms obtained by XPS measurement in the region from the outermost surface to a depth of 1 μm is 1.0% or less. The concentration of the above Si atoms is preferably 0.8% or less. Thereby, even when the surface is worn due to long-term use and the intermediate layer is exposed, the formation and adsorption of scale deposits can be suppressed.
[0103] As described above, for the purpose of increasing the density of the polymer, increasing the hydrophilicity, increasing the adhesion to the base material, etc., for example, Patent Document 1 discloses a technique for synthesizing a polymer containing zwitterions by silane coupling, and Patent Document 3 discloses a technique for providing a hydrophilic layer of 1 μm or less on the intermediate layer of a siloxane polymer. However, in these techniques, when the surface is worn due to long-term use of the member or structure, the Si component in the intermediate layer or the base material is exposed on the surface, making it easy to form scale deposits, so it is considered that the effect cannot be exerted in the long term.
[0104] The concentration of Si atoms in the region from the surface of the member to a depth of 1 μm can be measured by the following method.
[0105] <Gas Cluster Ion Beam - X-ray Photoelectron Spectroscopy (GCIB-XPS)> The surface layer is sputtered with Ar gas cluster ions, the surface exposed at each specific sputtering time is measured by XPS, and the concentration of Si atoms can be calculated.
[0106] <XPS Measurement> · Preparation of measurement sample A flat plate-shaped region cut from a component sample in an appropriate size can be used as a measurement sample. It is preferable to clean the surface of the measurement sample before measurement. For example, it is more preferable to clean the surface of the measurement sample using a neutral detergent and a sponge, then perform ultrasonic cleaning with ultrapure water, and finally thoroughly rinse with ultrapure water. ·XPS measurement device For the XPS measurement device, QUANTERA II (manufactured by ULVAC-PHI, Inc.) can be used. ·XPS measurement conditions X-ray conditions: Monochromatic AlKα ray, 25W - 15KV Photoelectron extraction angle: 45° Analysis area: 100μmφ Neutralization gun conditions: Auto Neutralizer Ion gun conditions: Auto Neutralizer (narrow) Time per step: 50ms Energy step size: 0.100eV Sweep: 5 times Pass energy: 55eV Scanning range: C1s peak 279.000eV - 299.000eV, O1s peak 525.000eV - 545.000eV, N1s peak 392.000eV - 410.000eV, S2p peak 157.000eV - 177.000eV, P2p peak 124.000eV - 144.000eV ·GCIB sputtering conditions The following conditions can be used for GCIB sputtering. Beam voltage: 10kV Beam current: 30nA
[0107] <Calculation of atomic concentration of Si> The atomic concentration of the detected elements can be calculated from the obtained spectrum using, for example, data analysis software MultiPaK (version 9.0, manufactured by ULVAC-PHI, Inc.). The spectrum obtained by XPS measurement is charge-corrected with the C1s peak set at 284.5 eV. After that, the background is removed by the Shirley method for the peaks based on the electron orbitals of each measured atom, and the peak area intensity is calculated. An analysis process is performed in which the peaks are divided by the sensitivity coefficient specific to the device that is preset in the data analysis software, and the atomic concentration of Si is calculated when the sum of C atoms, O atoms, N atoms, S atoms, Si atoms, and P atoms is set to 100%.
[0108] The sputter rate can be calculated by dividing the actual depth of the sputter marks on the sample after measurement, which is observed with a laser microscope, by the sputter time. Also, the depth at that point can be calculated by integrating the sputter time and the sputter rate.
[0109] <Protein adhesion area ratio> The protein adhesion inhibitory effect of the member according to the present invention can be indicated by using as an index the protein adhesion area ratio obtained according to the procedure described below.
[0110] (Preparation of protein-containing suspension) 2.5 g of commercially available wool keratin (Tokyo Chemical Industry Co., Ltd.) was mixed and suspended in 100 mL of ion-exchanged water, to which 0.25 g of triolein (Kanto Chemical Co., Ltd.) was added in order to increase the dispersibility of the keratin, and ultrasonic treatment was performed for 10 minutes in warm water at 40°C. Then, the mixture was centrifuged at 15,000 rpm for 10 minutes, and the supernatant was removed. Then, ultrasonic treatment was performed for 10 minutes in warm water at 40°C to obtain a suspension.
[0111] (Protein adhesion and cleaning) A plate-shaped area of an appropriate size can be cut from the component to be used as the measurement sample. The measurement sample should be 1 cm square or larger. The measurement sample is immersed in the above suspension for 10 minutes, and then the component is removed from the measurement sample. Then, ultrapure water is poured onto the surface of the measurement sample using a dropper at a concentration of 0.4 [mL / cm 2 ] and wash the sample. The sample is then tilted at a 25° angle and dried for one hour. This procedure is repeated twice to obtain a measurement sample with attached proteins.
[0112] (Observation of the surface of a measurement sample with proteins attached) Using a laser microscope LEXT OLS5000 (Olympus Corporation), select 117x magnification and standard mode (pitch 1.2 μm) to capture images of 2580 μm × 2580 μm per field of view. The specifications of the microscope are as follows: Equipment:OLS5000 Product Version: 1.2.1.4807 Light source: 405nm semiconductor laser Detection system: Photomultiplier Objective lens: OLYMPUS MPlan APO N 5X / 0.15 LEXT
[0113] The black structures seen in the captured images are attached proteins. The protein attachment area ratio can be calculated using the method shown below.
[0114] (Calculation of protein adhesion area ratio) The obtained images are used to calculate the protein adhesion area ratio using the image processing library "OpenCV" (version: 4.5.5). First, the image captured by the laser microscope is imported into the library, and after monochrome image processing, it is binarized. The threshold value for the binarization process is appropriately adjusted so that the attached protein is selected. From this, the total area ratio is calculated. This total area ratio is regarded as the protein adhesion area ratio.
[0115] The protein adhesion area rate of the member according to the present invention obtained as described above is preferably 8.3% or less, more preferably 5.0% or less, and even more preferably 1.0% or less.
[0116] Manufacturing method of components The member according to the present invention can be produced, for example, by the following method.
[0117] <Preparing the substrate> A substrate is prepared. In the present invention, it is preferable to pretreat the substrate. For example, it is preferable to wash the substrate with a neutral detergent and rinse with ion-exchanged water or ultrapure water. Any water droplets remaining on the substrate surface are preferably dried using an air blower or a dryer.
[0118] <Preparation of Composition for Forming Surface Layer> A compound having a structure represented by formula (A1) (a compound having a betaine structure) and other components are mixed in an arbitrary ratio and dissolved in a solvent. A polymerization initiator is added to this solution and stirred to obtain a composition for forming a surface layer. The weight concentration of the compound having a structure represented by formula (A1) is preferably 0.5% to 20%. When a polymerizable organic compound other than betaine is contained as an optional component, the total weight concentration of the compound having a structure represented by formula (A1) and the polymerizable organic compound other than betaine is preferably 0.5% to 20%, and the weight concentration ratio of each in the composition is preferably 95:5 to 5:95.
[0119] <Coating of the composition for forming the surface layer> The composition for forming a surface layer is applied onto the substrate. A known method may be used as the application method. For example, the composition can be applied by a general method such as brush coating, spray coating, dip coating, spin coating, curtain coating, bar coating, etc. The coating amount can be adjusted according to these application conditions to adjust the film thickness of the resulting cured product. In the present invention, the film thickness of the formed surface layer (or including both the surface layer and the intermediate layer) is preferably in the range of 0.1 μm to 200 μm. This provides a sufficient effect of suppressing the adhesion of proteins and the adhesion of water stains, and further allows the abrasion resistance to be exhibited. The film thickness of the surface layer (or including both the surface layer and the intermediate layer) is more preferably in the range of 1 to 100 μm, and even more preferably in the range of 1 to 20 μm.
[0120] <Drying> The surface layer forming composition applied on the substrate is dried. In the present invention, when the surface layer forming composition contains a solvent, it is preferable to dry the surface layer forming composition after applying it on the substrate in order to dry the solvent. In addition, in consideration of the productivity of the member, drying by heating can be preferably used.
[0121] <Curing> The surface layer forming composition applied on the substrate is cured. Examples of the curing means include heat curing, active energy ray curing, and a combination of heat curing and active energy ray curing. When heat curing is performed, a known thermal polymerization initiator can be used as the polymerization initiator, and a known method of heating with infrared rays or hot air can be used. In addition, in the case of active energy ray curing, examples of the radiation include visible light of 400 to 800 nm, ultraviolet light of 400 nm or less, and electron beams. Usually, relatively inexpensive ultraviolet light or visible light is preferably used rather than electron beams, which require expensive equipment. When active energy ray curing is performed using ultraviolet light or visible light, a known photopolymerization initiator can be used. When ultraviolet light is used, examples of the ultraviolet light generating source include low pressure mercury lamps, high pressure mercury lamps, ultra-high pressure mercury lamps, xenon lamps, gallium lamps, metal halide lamps, ultraviolet lasers, and ultraviolet light such as sunlight. The irradiation atmosphere may be air or an inert gas such as nitrogen or argon.
[0122] <Formation of the intermediate layer> In the present invention, the intermediate layer 3 may be formed on the substrate 1 before the surface layer 2 is formed on the substrate 1. This can further strengthen the adhesion between the substrate 1 and the surface layer 2. The composition for forming the intermediate layer can be prepared, for example, by adding a polymerization initiator to a solution in which the monomer capable of forming the above-mentioned polyacrylic or polyvinyl copolymer and a solvent are dissolved at an arbitrary weight ratio, and then stirring the solution. The intermediate layer 3 can then be formed by applying the prepared composition for forming the intermediate layer on the substrate 1, drying, and curing it.
[0123] The thickness of the intermediate layer can be adjusted by the coating conditions, similarly to the surface layer. In the present invention, the thickness of the formed intermediate layer (or including both the surface layer and the intermediate layer) is preferably in the range of 0.1 μm to 200 μm. This provides a sufficient effect of suppressing the adhesion of proteins and the adhesion of water stains, and further allows abrasion resistance to be exhibited. The thickness of the intermediate layer (or including both the surface layer and the intermediate layer) is more preferably in the range of 1 to 100 μm, and even more preferably in the range of 1 to 20 μm.
[0124] <Formation of primer layer> In the present invention, when the substrate 1 is an inorganic material such as glass, pottery, or metal, a primer layer 4 may be formed on the inorganic substrate before forming an intermediate layer 3 on the inorganic substrate. This can further strengthen the adhesion between the inorganic substrate and the surface layer 2. The composition for forming a primer layer can be prepared, for example, by dissolving the above-mentioned coupling agent and a solvent, and, if necessary, a catalyst for promoting the hydrolysis reaction in an arbitrary weight ratio, and stirring the mixture. Thereafter, the prepared composition for forming a primer layer can be applied to the inorganic substrate and dried to form the primer layer 4. EXAMPLES
[0125] The present invention will be described in more detail with reference to the following examples, although the present invention is not limited to these examples.
[0126] 1. Preparation 1-1. Base material The following five types of substrates were prepared. Acrylic plate: Acrylite EX (manufactured by Mitsubishi Rayon Co., Ltd.) PET film: Lumirror Film T60 (manufactured by AS ONE Corporation) Glass: borosilicate glass · Ceramic: Sanitary ware with a glaze layer on the surface Metal: Brass plate with nickel-chrome plating on the surface
[0127] 1-2.Reagents The following reagents were prepared:
[0128] <Multifunctional acrylate> · Multifunctional acrylate 1: Dipentaerythritol polyacrylate
[0129] <Polymerization initiator> A mixture of 1-hydroxycyclohexyl phenyl ketone and benzophenone in a weight ratio of 1:1 (BASF Irgacure 500)
[0130] <Solvent> 2-Methoxyethanol
[0131] <Compounds with betaine structure> Betaine Monomer 1: 3-[[2-(methacryloyloxy)ethyl]dimethylammonio]propane-1-sulfonic acid Betaine Monomer 2: 4-[(3-methacrylamidopropyl)dimethylammonio]butane-1-sulfonic acid Betaine monomer 3: 2-(methacryloyloxy)ethyl 2-(trimethylammonio)ethyl phosphate
[0132] <Nonionic monomer> Non-ionic monomer 1: 2-hydroxyethyl methacrylate (HEMA) Nonionic monomer 2: 2-Methoxyethyl acrylate Non-ionic monomer 3: Methoxypolyethylene glycol methacrylate Non-ionic monomer 4: Methoxytetraethylene glycol methacrylate Non-ionic monomer 5: 2-hydroxybutyl methacrylate Non-ionic monomer 6: Diethylene glycol dimethacrylate Non-ionic monomer 7: Butyl methacrylate
[0133] <Anionic Monomer> Anionic Monomer 1: Potassium 3-((meth)acryloyloxy)propane-1-sulfonate Anionic Monomer 2: Sodium 2-acrylamido-2-methylpropanesulfonate
[0134] <Cationic Monomer> Cationic monomer 1: Trimethyl-2-methacryloyloxyethyl ammonium chloride
[0135] <Silane compounds> Silane compound 1: 3-acryloxypropyltrimethoxysilane Silane compound 2: 3-methacryloxypropyltrimethoxysilane Silane compound 3: Tetraethoxysilane
[0136] <Surfactant> Surfactant 1: Sodium di-2-ethylhexyl sulfosuccinate (Aerosol OT) The standard content was 75% by weight.
[0137] 2. Preparation of component samples Examples 1 to 7, 9 to 15, 20 to 24 <Pretreatment> The surface of the acrylic plate, which is the substrate, was washed with a neutral detergent and rinsed with ion-exchanged water or ultrapure water. Water droplets on the surface of the substrate were blown off with an air blower, and the substrate was dried in a dryer at 60°C for 30 minutes.
[0138] <Middle Class> A polymerization initiator was added at a weight concentration of 0.6% to a solution of multifunctional acrylate:solvent = 33:67 (weight ratio), and the mixture was stirred with a stirrer for 1 hour to prepare a composition for forming an intermediate layer. This composition was applied to the pretreated substrate by spin coating (1500 rpm, 15 seconds) or bar coating (#10) as shown in Table 1. Immediately after application, the substrate was placed in a hot air drying oven and allowed to stand at 60°C for 10 minutes. Thereafter, an ultraviolet ray irradiation device (MDB15001N-01, SunEnergy Co., Ltd.) was used to irradiate the substrate with an accumulated light dose of 1000 mJ / cm. 2The applied surface was irradiated with UV light to cure so that the viscosity reached 100 ppm (measured using an ultraviolet integrating light meter, C9536-254, manufactured by Hamamatsu Photonics K.K.).
[0139] <Surface layer> A compound having a betaine structure shown in Table 1 and a polymerizable organic compound other than betaine were mixed in an arbitrary ratio and dissolved in a solvent so that the total of these was 10% by weight. A polymerization initiator was added to this solution at a weight concentration of 0.2% and stirred with a stirrer for 1 hour to prepare a composition for forming a surface layer. This composition was applied to the intermediate layer by spin coating (1500 rpm, 15 seconds) or bar coating (#10) as shown in Table 1. Immediately after application, the composition was placed in a hot air drying oven and left to stand at 60°C for 10 minutes. Thereafter, an ultraviolet irradiation device (MDB15001N-01, manufactured by SunEnergy Co., Ltd.) was used to obtain an integrated light dose of 3 J / cm. 2 The applied surface was irradiated with UV light to cure so that the viscosity reached 100 ppm (measured using an ultraviolet integrating light meter, C9536-254, manufactured by Hamamatsu Photonics K.K.).
[0140] To remove uncured components, the specimen was washed with a neutral detergent, rinsed with ion-exchanged water or ultrapure water, and then left to dry at room temperature for at least 1 hour to obtain a component sample.
[0141] Example 16 A component sample was obtained in the same manner as in Example 1, except that the acrylic plate was replaced with a PET film as the substrate.
[0142] Examples 17 to 19 <Pretreatment> The inorganic substrates shown in Table 1 were used as substrates, and the substrate surfaces were activated by UV ozone treatment after drying in the same pretreatment as in Example 1. The UV ozone treatment was performed by irradiating UV ozone for 10 minutes using a UV ozone irradiation device (manufactured by Asumi Giken Co., Ltd.).
[0143] <Primer layer> A mixture of silane compound (1 or 2): 10 wt% aqueous acetic acid solution: ethanol = 0.5:2:97.5 (weight ratio) was stirred with a stirrer at room temperature for 1 hour to prepare a composition for forming a primer layer. Then, this composition was applied to the surface of the inorganic substrate with a bar coat (#10) as shown in Table 1, and dried in a dryer at 50°C for 5 minutes and then at 120°C for 30 minutes to form a primer layer. After this, an intermediate layer and a surface layer were produced in this order by the same manufacturing method as in Example 1, and a component sample was obtained.
[0144] Example 8 Compound 1 having a betaine structure at 0.3%, nonionic monomer 3 at 0.7%, polyfunctional acrylate at 30%, polymerization initiator at 0.75%, and surfactant 1 at 0.1% were dissolved in a solvent, stirred with a stirrer for 1 hour, and applied to the substrate with a bar coater (#24). Immediately after application, the substrate was placed in a hot air drying oven and allowed to stand at 60°C for 10 minutes. After that, an ultraviolet irradiation device (MDB15001N-01, SunEnergy Co., Ltd.) was used to irradiate the substrate with an accumulated light dose of 1000 mJ / cm. 2 The coated surface was irradiated with UV light to cure so that the curing temperature reached 100°C (measured with an ultraviolet integrating light meter, C9536-254, manufactured by Hamamatsu Photonics K.K.). To remove any uncured components, the surface was washed with a neutral detergent, rinsed with ion-exchanged water or ultrapure water, and then left to dry at room temperature for at least one hour to obtain a component sample.
[0145] Comparative Examples 1 to 4 Each component sample of Comparative Examples 1 to 4 was obtained in the same manner as in Example 1, except that only betaine monomer 1, nonionic monomer 1, anionic monomer 1, and cationic monomer 1 shown in Table 1 were used as the surface layer forming composition.
[0146] Comparative Example 5 In the production method of Example 1, as the composition for forming the surface layer, in addition to betaine monomer 1 and nonionic monomer 1, silane compound 3 was further added, and the total of these was dissolved in a solvent so as to have a weight concentration of 10%. A polymerization initiator was added later to this solution at a weight concentration of 0.2%, and the mixture was stirred with a stirrer for 1 hour to prepare a composition for forming the surface layer. Thereafter, a member sample was obtained by the same production method as in Example 1.
[0147] Comparative Examples 6 to 7 The acrylic plate and glass as the base materials were used as the member samples of Comparative Examples 6 and 7 as they were.
[0148] 3. Evaluation and Results 3-1.XPS evaluation <Preparation of Evaluation Samples> A region of about 1 cm square size was cut from the plate-shaped member sample and used as a measurement sample. Before measurement, the surface of the measurement sample was washed to sufficiently remove the dirt adhering to the surface. Specifically, it was slid and washed with a sponge using a neutral detergent, then ultrasonically washed in ultrapure water at room temperature for 10 minutes, and then sufficiently rinsed with ultrapure water.
[0149] <XPS Measurement> ·XPS measurement apparatus K-alpha (manufactured by ThermoFisher Scientific Co., Ltd.) was used. ·XPS measurement conditions X-ray conditions: Monochromatized AlKα ray, 72W - 12KV Photoelectron extraction angle: 90° Analysis region: 400μmφ Neutralization gun conditions: 200μA Ion gun conditions: 10mA (Survey) Time per step: 10ms Energy step size: 1.000eV Sweep: 2 times Pass energy: 200eV Scanning range: -10~1350eV (Narrow) Time per step: 50 ms Energy step size: 0.100 eV Sweep: 5 times Pass energy: 50 eV Scanning range: C1s peak 279.000 eV - 298.000 eV, O1s peak 525.000 eV - 545.000 eV, N1s peak 392.000 eV - 410.000 eV, S2p peak 157.000 eV - 175.000 eV, Si2p peak 95.000 eV - 110.000 eV, P2p peak 124.000 eV - 144.000 eV
[0150] <(S, N, Si, P) atomic concentrations of each atom> The atomic concentrations of the detected elements were calculated from the obtained spectra using the data analysis software Thermo Avantage (version 5.9916, manufactured by Thermo Fisher Scientific Co., Ltd.). First, using the spectra obtained from the survey analysis, it was confirmed whether the cleaning was properly done. For the spectra obtained from the narrow analysis, after charge correction with the C1s peak set at 284.5 eV, the background was removed by the Smart method for the peaks based on the electron orbits of each measured atom, then the peak area intensity was calculated, and an analysis process of dividing by the sensitivity coefficient specific to the device preset in the data analysis software was performed to calculate the atomic concentrations of C atoms, O atoms, N atoms, S atoms, Si atoms, and P atoms when the total of these atoms was set to 100%. The results are shown in Table 1.
[0151] <Peak separation of N atoms> To separate the peak derived from the +1 valence N atom (N + ) contained in the betaine structure from the peak derived from other 0 valence N atoms (N 0 ), the following method was used. The peak position of N + was fixed at 401.4 - 401.8 eV and the full width at half maximum of the peak was fixed at 1.6 eV, and the peak position of N 0 was fixed at 398.7 - 399.4 eV, and peak fitting was performed. When the total of C atoms, O atoms, N atoms, S atoms, Si atoms, and P atoms was set to 100%, the N+ , N 0 The atomic concentrations of each of them are shown in Table 1.
[0152] GCIB-XPS evaluation <Preparation of Evaluation Samples> A region with a size of about 1 cm square was cut from a plate-shaped member sample and used as a measurement sample. Before measurement, the surface of the measurement sample was cleaned to sufficiently remove the dirt adhering to the surface. Specifically, it was slid and cleaned with a sponge using a neutral detergent, then ultrasonically cleaned in ultrapure water at room temperature for 10 minutes, and then thoroughly rinsed with ultrapure water. ·XPS Measurement Device QUANTERA II (manufactured by ULVAC-PHI, Inc.) was used as the XPS measurement device. ·XPS Measurement Conditions X-ray Conditions: Monochromatized AlKα ray, 25W - 15KV Photoelectron Extraction Angle: 45° Analysis Region: 100μmφ Neutralization Gun Conditions: Auto Neutralizer Ion Gun Conditions: Auto Neutralizer (Narrow) Time per step: 50ms Energy step size: 0.100eV Sweep: 5 times Pass energy: 55eV Scanning Range: C1s peak 279.000eV - 299.000eV, O1s peak 525.000eV - 545.000eV, N1s peak 392.000eV - 410.000eV, S2p peak 157.000eV - 177.000eV, P2p peak 124.000eV - 144.000eV ·GCIB Sputtering Conditions The following conditions were used for GCIB sputtering. Beam Voltage: 10kV Beam Current: 30nA
[0153] <Calculation of Atomic Concentration of Si> The atomic concentrations of the detected elements were calculated from the obtained spectra using the data analysis software MultiPaK (Version 9.0, ULVAC-PHI, Inc.). The obtained spectra were charge-corrected with the C1s peak at 284.5 eV. After that, the background was removed by the Shirley method for the peaks based on the electron orbitals of each measured atom, and the peak area intensity was calculated. The data analysis software was then divided by the device-specific sensitivity coefficient preset in the data analysis software to calculate the atomic concentration of Si when the sum of C, O, N, S, Si, and P atoms was taken as 100%.
[0154] The sputtering rate was calculated by dividing the actual depth of the sputtered mark on the sample after measurement by the sputtering time. The depth at that point was calculated by integrating the sputtering time and the sputtering rate.
[0155] 3-3.Contact angle The static contact angle of water with respect to the surface of the surface layer was measured under the following measurement conditions using the following device and software. The results are shown in Table 1. Equipment: DMo-702 (Kyowa Interface Science Co., Ltd.) Software: FAMAS integrated interface measurement / analysis system Version:7.3.0 Measurement method: Droplet method Droplet volume: 2.0μL Waiting time: 1000ms Analysis method: θ / 2 method
[0156] 3-4. Evaluation of water stain removal performance <Creating limescale> 20 μL of tap water (Chigasaki, Kanagawa Prefecture) was dropped onto the surface of each component sample using a micropipette, and the sample was placed in a thermostatic chamber (manufactured by Espec Corporation) and left to stand at 25°C and a relative humidity of 75% for 24 hours to obtain samples with water stains formed.
[0157] <Cleaning evaluation> The obtained samples were evaluated for their ability to clean water stains using the following method. Using a sliding machine (manufactured by Tester Sangyo Co., Ltd.), the sliding load was gradually increased and the surface on which water stains had formed was slid at the following levels. The sample surface was then visually observed, and the level at which the water stains were no longer visible was evaluated as the water stain cleaning ability of that sample. The results are shown in Table 1.
[0158] Level 6: A commercially available urethane sponge (Scotch-Brite Bath Shine, manufactured by 3M Japan Co., Ltd.) is soaked in water and subjected to a load of 25 g / cm 2 ] 5 round trips Level 5: A commercially available urethane sponge (Scotch-Brite Bath Shine, manufactured by 3M Japan Co., Ltd.) is soaked in water and subjected to a load of 50 g / cm 2 ] 5 round trips Level 4: A commercially available urethane sponge (Scotch-Brite Bath Shine, manufactured by 3M Japan Co., Ltd.) was soaked in a mixture of water and neutral detergent (Bath Magiclean, manufactured by Kao Corporation) in a weight ratio of 90:10, and subjected to a load of 25 [g / cm 2 ] 5 round trips Level 3: A commercially available urethane sponge (Scotch-Brite Bath Shine, 3M Japan) was soaked in water and a neutral detergent (Bath Magiclean, Kao Corporation) in the same ratio as in Level 4, and subjected to a load of 50 g / cm 2 ] 5 round trips Level 2: A commercially available urethane sponge (Scotch-Brite Bath Shine, manufactured by 3M Japan Co., Ltd.) was soaked in water and a neutral detergent (Bath Magiclean, manufactured by Kao Corporation) mixed in the same ratio as in Level 4, and subjected to a load of 90 [g / cm 2 ] 25 round trips Level 1: A commercially available urethane sponge (Scotch-Brite Bath Shine, manufactured by 3M Japan Co., Ltd.) was soaked in water and an abrasive cleaner (Kiraria, manufactured by TOTO Co., Ltd.) and subjected to a load of 50 g / cm 2 ] 5 round trips Level 0: Cannot be obtained even at level 1
[0159] 3-5. Protein adsorption evaluation <Preparation of protein-containing suspension> 2.5 g of commercially available wool keratin (Tokyo Chemical Industry Co., Ltd.) was mixed and suspended in 100 mL of ion-exchanged water, to which 0.25 g of triolein (Kanto Chemical Co., Ltd.) was added in order to increase the dispersibility of the keratin, and the mixture was subjected to ultrasonic treatment for 10 minutes in warm water at 40°C. The mixture was then centrifuged at 15,000 rpm for 10 minutes, and the supernatant was removed. The mixture was then subjected to ultrasonic treatment for 10 minutes in warm water at 40°C to obtain a suspension.
[0160] <Protein adhesion and cleaning> A measurement sample was prepared by cutting an area of approximately 1 cm square from a plate-shaped component sample. The measurement sample was immersed in the above suspension for 10 minutes, and then removed from the suspension. Then, ultrapure water was poured onto the surface of the measurement sample using a dropper at a concentration of 0.4 [mL / cm 2 ] and washed. The measurement sample was then tilted at an angle of 25° and dried for one hour. This procedure was repeated twice to obtain a measurement sample with keratin attached.
[0161] <Observation of the surface of a measurement sample with proteins attached> Using a laser microscope LEXT OLS5000 (Olympus Corporation), a magnification of 117 times and standard mode (pitch 1.2 μm) were selected, and images of 2580 μm × 2580 μm per field of view were taken. The specifications of the microscope are as follows. Equipment:OLS5000 Product Version: 1.2.1.4807 Light source: 405nm semiconductor laser Detection system: Photomultiplier Objective lens: OLYMPUS MPlan APO N 5X / 0.15 LEXT
[0162] The photographed images are shown in Figures 2 and 3. Figure 2 is an image of the measurement sample of Example 1, and Figure 3 is an image of the measurement sample of Comparative Example 2. The black structures seen in the images are attached proteins. The protein attachment area ratio was calculated by the method shown below.
[0163] <Calculation of protein adhesion area ratio> The obtained images were used to calculate the protein adhesion area ratio using the image processing library "OpenCV" (version: 4.5.5). First, the images taken with a laser microscope were imported into the library, and after monochrome image processing, binarization was performed. The threshold value for the binarization process was appropriately adjusted so that the attached protein was selected. From this, the total area ratio was calculated. This total area ratio was taken as the protein adhesion area ratio. The results are shown in Table 1.
[0164] <Sliding durability evaluation> A sliding durability test was carried out on the member samples of Example 2 and Comparative Example 5 using a sliding machine (manufactured by Tester Sangyo Co., Ltd.). A commercially available urethane sponge (Scotch-Brite Bath Shine, manufactured by 3M Japan Co., Ltd.) was soaked in a mixture of water and neutral detergent (Bath Magiclean, manufactured by Kao Corporation) in a weight ratio of 90:10, and was moved back and forth over the surface of the sample 5,000 times with a load of 25 g / cm2. After washing the sample with running water, it was dried, and the static contact angle of water was measured using the method described above. The sliding durability was evaluated according to the following criteria. ○: The static contact angle of water after the sliding test is 35 degrees or less ×: The static contact angle of water after the sliding test is greater than 35 degrees.
[0165] As a result, the static contact angle of water after the sliding durability test in the member sample of Example 2 was 12.0 degrees and was evaluated as ◯, whereas the static contact angle of water after the sliding durability test in the member sample of Comparative Example 5 was 40.2 degrees and was evaluated as ×.
[0166] <Film thickness evaluation> The member sample of Example 2 was cut in the cross-sectional direction. The thickness of the cut portion, including the intermediate layer and the surface layer, was measured using a scanning electron microscope, and found to be 6 μm. The scanning electron microscope used was as follows: Equipment: Regulus8220 (Hitachi High-Tech Corporation) Acceleration voltage: 1kV Magnification: 6000x
[0167] [Table 1] [Explanation of symbols]
[0168] 10. Materials 1 Base material 2 Surface layer 3. Middle Tier 4 Primer layer
Claims
1. A member used in an environment where water and contaminants including organic and inorganic components adhere to a surface, and the water dries while the water and contaminants are mixed on the surface, the cycle being repeated, The member includes a substrate and a surface layer, The surface layer includes a structure represented by the following formula (A1): 【Chemistry 1】 In formula (A1), L 1 is -COO-, -CONH-, -(CH 2 ) m - (where m is a natural number), R 1 is H or CH 3 and X 1 is a functional group represented by the following formula (B1) or the following formula (B2), 【Chemistry 2】 【Chemistry 3】 In formula (B1), R 3 and R 6 Each independently represents -(CH 2 ) l - (l is a natural number from 1 to 10), R 4 and R 5 each independently represents an organic group containing C and H as essential components and O as an optional component, and not containing N or S, In formula (B2), R 7 and R 8 Each independently represents -(CH 2 ) l - (l is a natural number from 1 to 10), R 9 , R 10 , R 11 each independently represents an organic group containing C and H as essential components and O as an optional component, and not containing N or S, The surface of the component is measured by X-ray photoelectron spectroscopy (XPS): ・N + N atoms belonging to + The concentration of 0.3% or more and 2.8% or less of the cations (referred to as "atoms") is 0.3% or more and 2.8% or less; the concentration of S atoms, the concentration of P atoms, or the sum of the concentration of S atoms and the concentration of P atoms is 0.3% or more; and The concentration of Si atoms is 1.0% or less, The concentration of Si atoms obtained by measuring the region from the surface of the member to a depth of 1 μm using X-ray photoelectron spectroscopy (XPS) is 1.0% or less. A member characterized in that
2. The X 1 The member according to claim 1 , characterized in that:
3. 3. The member according to claim 1, wherein the static contact angle of water with respect to the surface of the surface layer is 35° or less.
4. The member according to claim 1 or 2, wherein the surface layer comprises a random copolymer having a structure represented by formula (A1) and a structure containing an organic component other than the structure represented by formula (A1).
5. The member according to claim 3 , wherein the surface layer comprises a random copolymer having a structure represented by formula (A1) and a structure containing an organic component other than the structure represented by formula (A1).
Citation Information
Patent Citations
Composition for forming hydrophilic membrane and hydrophilic member
JP2008239949A
Curable composition, coating, and laminate
WO2017018146A1
Hydrophilic resin composition and laminated sheet
WO2018079592A1
Hydrophilic structure and production method for hydrophilic structure
WO2018155577A1